Angiogenesis versus arteriogenesis: neuropilin 1 modulation of VEGF signaling - Kofler, Natalie M. (F1000Prime Rep, 2015)
In development and disease, vascular endothelial growth factor (VEGF) regulates the expansion of the vascular tree. In response to hypoxia, VEGF promotes new capillary formation through the process of angiogenesis by inducing endothelial cell sprouting, proliferation, and migration. Wound healing, tissue regeneration, and tumor growth depend on angiogenesis for adequate nutrient and oxygen delivery. Under different conditions, VEGF promotes arterial growth, modulates lumen expansion, and induces collateral vessel formation, events collectively referred to as arteriogenesis. Induction of arteriogenesis after cardiac or cerebral arterial occlusion can reduce ischemia and improve disease outcome. Endothelial VEGF receptor 2 (VEGFR2) signaling governs both processes. However, modulation of downstream VEGF signaling effectors, such as extracellular-signal-regulated kinase (ERK) activation, differs in order to achieve angiogenic versus arteriogenic outcomes. Recent reports show that neuropilin 1 (NRP1), a VEGF receptor, can instill VEGF signaling outcomes that specifically regulate either angiogenesis or arteriogenesis. Here, we discuss how NRP1 functions as a VEGFR2 co-receptor in angiogenesis and a modulator of VEGFR2 trafficking in arteriogenesis. The unique role played by neuropilin in different endothelial processes makes it an exciting therapeutic target to specifically enhance angiogenesis or arteriogenesis in disease settings.